Epidemiology and Clinical Characteristics of Pediatric Chronic Kidney Disease in Iraq: A Focus on Preventable Etiologies and Late-Stage Presentation - Ghareeb, Dr. Safa Raad; Ahmed, Dr. Mohammed kareem (Journal of Science in Medicine and Life, 2025)
Children who suffer from Chronic Kidney Disease (CKD) experience a progressive condition because of either congenital urological abnormalities or acquired malformations which results in severe morbidity. Outcomes require early identification and appropriate management to prevent complications from occurring. The research goal was to analyze pediatric CKD patient demographics together with etiology and clinical manifestations and laboratory test outcomes at Al-Imamain Al-Kadhimaian Medical City during Jan 2025 to March 2025. A descriptive cross-sectional study about pediatric CKD patients analyzed 30 participants. The research obtained data about patient demographics, residence, kidney disease duration, kidney failure type and glomerular filtration rate (GFR), hemoglobin levels, blood pressure, and chronic kidney disease (CKD) stage from medical files. The researchers performed statistical analysis through descriptive methods. Most patients exceeded ten years of age (63.3% of the study group) and males made up 55% of the total participants. Urban residency was more common (75%). The main causes of CKD in children were recurrent urinary tract infections experienced by 50% of patients and vesicoureteral reflux discovered in 25% of cases. About sixty percent of patients showed reduced glomerular filtration rate which was diagnosed as less than 90 mL/min/1.73 m² and forty-one percent of these patients were classified in Stage 3 CKD. The research showed Anemia affected 96.7% of patients and hypertension existed in 33.3% of patients. The evaluated cases showed that cardiovascular disease occurred as a comorbidity in 30% of patients. Most pediatric patients with CKD in this study population developed their condition due to preventable causes particularly UTIs and VUR but received diagnoses in moderate to advanced disease stages. Early detection alongside better urological treatments with focused intervention strategies must be promoted to improve patient outcomes because hypertension and anemia exist at high levels.